Health Anxiety and Its Relationship to Disability and Service Use: Findings From a Large Epidemiological Survey. Issue 1 (January 2016) - Bobevski, Irene; Clarke, David M.; Meadows, Graham
ABSTRACT: Objective: To explore the contribution of health anxiety to disability and use of mental health and medical services, independently of co-occurring mental and physical conditions. Methods: Data from the Australian National Survey of Mental Health and Wellbeing 2007 were analyzed ( n = 8841). Participants were aged 16 to 85 years (mean [standard deviation] = 46.3 [19.0] years) and 54% were women. Results: Health anxiety accounted independently for high disability and service use. People with health anxiety were more likely to use both mental health (for psychiatrists: odds ratio [OR] = 2.1, 95% confidence interval [CI] = 1.2–3.5; for psychologists: OR = 1.9, 95% CI = 1.2–3.3) and specialist medical services (OR = 1.7, 95% CI = 1.2–2.3) than people without health anxiety. However, they were not high-frequency attenders to specialist mental health services (OR = 1.6 [95% CI = 0.9–3.0] and OR = 1.3 [95% CI = 0.6–2.9]) compared with people with other mental disorders (OR = 11.7 [95% CI = 4.3–31.8] and OR = 29.5 [95% CI = 13.5–64.6] for psychiatrists and psychologists, respectively). People with health anxiety were likely to be high-frequency attenders to general practice (OR = 2.0, 95% CI = 1.4–2.8) and specialist medical services (OR = 2.4, 95% CI = 1.7–3.6). Conclusions: It is important to recognize and treat health anxiety, even when coexisting with other conditions, to prevent high disability burden and excessive service use. The cross-sectional design and self-reported outcomes may have resulted in overestimation of the associations. Future work is needed on actual service use using reviews of medical records.